2022
DOI: 10.1093/rheumatology/keac192
|View full text |Cite
|
Sign up to set email alerts
|

Soluble LILRA3 is aberrantly expressed in antiphospholipid syndrome (APS) and is a potential marker of thrombotic APS

Abstract: Objective Leucocyte immunoglobulin-like receptor A3 (LILRA3) belongs to a family of leucocyte receptors. Our previous study reported LILRA3 transcripts were markedly upregulated in neutrophils from patients with antiphospholipid syndrome (APS). We undertook this study to investigate clinical implications of LILRA3 in APS and its potential role in APS-associated thrombosis. Methods Two independent cohorts were studied. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…By evaluating the expression of pro-NETosis genes ( PADI4 , ELANE , and MPO ), as well as circulating NET remnants (citrullinated histone H3 and myeloperoxidase-DNA complexes), the authors found a pronounced association between thrombotic APS (particularly those patients with triple aPL positivity or recurrent thrombosis) and increased NET formation [68 ▪ ]. An additional 2022 study also found that leukocyte immunoglobulin receptor A3 (LILRA3) was significantly increased in patients with thrombotic APS [69 ▪▪ ]. Furthermore, it was shown that LILRA3 was positively correlated with myeloperoxidase–DNA complexes (NET remnants) in patients with LILRA3-positive thrombotic APS [69 ▪▪ ].…”
Section: Neutrophils and Neutrophil Extracellular Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…By evaluating the expression of pro-NETosis genes ( PADI4 , ELANE , and MPO ), as well as circulating NET remnants (citrullinated histone H3 and myeloperoxidase-DNA complexes), the authors found a pronounced association between thrombotic APS (particularly those patients with triple aPL positivity or recurrent thrombosis) and increased NET formation [68 ▪ ]. An additional 2022 study also found that leukocyte immunoglobulin receptor A3 (LILRA3) was significantly increased in patients with thrombotic APS [69 ▪▪ ]. Furthermore, it was shown that LILRA3 was positively correlated with myeloperoxidase–DNA complexes (NET remnants) in patients with LILRA3-positive thrombotic APS [69 ▪▪ ].…”
Section: Neutrophils and Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…Furthermore, it was shown that LILRA3 was positively correlated with myeloperoxidase–DNA complexes (NET remnants) in patients with LILRA3-positive thrombotic APS [69 ▪▪ ]. After treatment, the levels of LILRA3 and myeloperoxidase-DNA complexes were consistently decreased amongst these patients, suggesting that LILRA3 might eventually be leveraged as a biomarker or therapeutic target in thrombotic APS [69 ▪▪ ].…”
Section: Neutrophils and Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…По данным других авторов, наблюдается выраженная ассоциация между «тромботическим» подтипом АФС (тройная позитивность по аФЛ и рецидивирующий тромбоз) и увеличением образования компонентов NETs (цитруллинированный гистон Н3 и МПО-ДНК комплексы) [144]. Увеличение экспрессии LILRA3 (leukocyte immunoglobulin like receptor A3), участвующего в регуляции иммунного ответа, положительно коррелирует с формированием комплексов МПО-ДНК и развитием тромботического субтипа АФС [145].…”
Section: антифосфолипидный синдромunclassified